Factors of influence of leaders’ organizational and pedagogical activity on choice of development strategy in secondary schools - Кудляк, Світлана Миколаївна (Pedagogy of Higher and Secondary Education, 2017)
The article shows the main aspects of school system updating which defined the need to review approaches to the management of educational institutions and improve the methods of work planning in accordance with modern requirements. The modernization and optimization of management, any socio-educational system, provides a deep analysis of the situation and introspection, review of modern views on the existing problem, identifying areas of change and ways to implement them. That will help improve the management system of the educational process in schools and choose the strategy of modern school development, implement fully predictive function of school management. It is stated that the development strategy of an educational institution is to ensure the unity of action of the administration, teaching staff and nongovernmental organizations, schools, consistent implementation of measures to strengthen labor discipline, rational organization of teachers, increasing their responsibility for the outcome of educational work, creating a pedagogical team atmosphere, creative pedagogical search.Thus, planning provides an opportunity to properly orient all management activities to avoid the factors that negatively affect the educational institution; identify the causes of management and teaching activities, help to achieve good results, save time. That is why the head of an educational institution is responsible for mastering innovative approaches to planning.Taking into account a literature analysis and considering the relevance of research it can be noted that the determination of factors of influence of organizational and pedagogical activities enables choosing the strategy of educational institution, deep understanding of the role of helmsman modern school in establishing a society of positive image.